A Bayesian perspective on delusions: Suggestions for modifying two reasoning tasks. (September 2017) - Pfuhl, Gerit
Abstract: Background and objectives: There are a range of mechanistic explanations on the formation and maintenance of delusions. Within the Bayesian brain hypothesis, particularly within the framework of predictive coding models, delusions are seen as an aberrant inference process characterized by either a failure in sensory attenuation or an aberrant weighting of prior experience. Testing of these Bayesian decision theories requires measuring of both the patients' confidence in their beliefs and the confidence they assign new, incoming information. In the Bayesian framework we apply here, the former is referred to as the prior while the latter is usually called the data or likelihood. Methods and results: This narrative review will commence by giving an introduction to the basic concept underlying the Bayesian decision theory approach to delusion. A consequence of crucial importance of this sketch is that it provides a measure for the persistence of a belief. Experimental tasks measuring these parameters are presented. Further, a modification of two standard reasoning tasks, the beads task and the evidence integration task, is proposed that permits testing the parameters from Bayesian decision theory. Limitations: Patients differ from controls by the distress the delusions causes to them. The Bayesian Decision theory framework has no explicit parameter for distress. Conclusions: A more detailed reporting of differences between patients with delusions is warranted. Highlights: Brief introduction of Bayesian decision theory account of delusion. Reliability and precision of belief illustrated. Belief formation and maintenance derived from aberrant reliability and precision. Modification of two reasoning tasks suggested.